The role of thyroid radiation carcinogenesis in rats - Koritnik, Katarina (Radiology and oncology (Ljubljana), 1998)
The aimof this study was to test the hypothesis on the protective role of thyroxin administration before and during irradiation on the occurrence of thyroid carcinoma in rats. Application of thyroxin before and during irradiation was expected to decrease production of thyrotropin by the hypophyseal feedback mechanism, caused by radiation damage of thyroid tissue. Stabilizing the thyroid cells in this way during irradiation would thus make them less radiosensitive. In the experiment, we first divided 81 three to fourweek old Wistar strain rats of both sexes into two groups, i.e. thyroxin (T4) and water (H2O). The T4 rats were injected 1% thyroxin solution (0.01 mg/100 g body weight) twice a day for 15 days, while the H2O rats received saline in the same way. After ten days, the two main groups were divided each into two subgroups. The rats from both irradiated subgroups (T4/X and (H2O/X) recieved 10 Gy to the neck area. They were iradiated with a telecobalt machinefor five consecutive days with one direct field. During a two years follow - up, all moribund animals were sacrificed and their thyroid glands taken. The rest of the thyroid glands were taken at the end of the experiment.All glands were pathohistologically analysed. Besides, all suspicious and enlarged extrathyroid organs and tissues were examined and the occurrence of tumors was noted. Pathohistological examination revealed the occurrence of 8 thyroid carcinomas and 7 adenomas in the H2O/X group, and 3 adenomas in the T4/X group. In the iradiated group of rats without thyroxin, significantly (P = 0.01) more thyroid carcinomas occurred than in the irradiated group without thyroxin.
Keywords: Neoplasms, radiation-induced; Pathology; poskusi na živalih; rak (medicina); Rats, wistar; ščitnica; Therapeutic use; Thyroid neoplasms; Thyroxine; tiroksin; zdravljenje